1998
DOI: 10.1073/pnas.95.4.1899
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression of the human Δ7-sterol reductase

Abstract: Inhibitors of the last steps of cholesterol biosynthesis such as AY9944 and BM15766 severely impair brain development. Their molecular target is the ⌬7-sterol reductase (EC 1.3.1.21), suspected to be defective in the Smith-Lemli-Opitz syndrome, a frequent inborn disorder of sterol metabolism. Molecular cloning of the cDNA revealed that the human enzyme is a membrane-bound protein with a predicted molecular mass of 55 kDa and six to nine putative transmembrane segments. The protein is structurally related to pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
166
0
5

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(177 citation statements)
references
References 29 publications
6
166
0
5
Order By: Relevance
“…5 Molecular cloning, expression of human ∆7-sterol reductase cDNA (DHCR7) and mutational analysis of the DHCR7 gene in SLOS patients have been recently reported. [6][7][8][9] Nineteen different mutations of DHCR7, mostly missense mutations, have been described in 19 SLOS patients to date. Although a clear-cut phenotype/ genotype correlation cannot be established, homozygosity for mutations resulting in a severe disruption of DHCR7, eg those affecting the highly conserved carboxyl-terminal part of the protein, seems to cause the SLOS type II.…”
Section: Introductionmentioning
confidence: 99%
“…5 Molecular cloning, expression of human ∆7-sterol reductase cDNA (DHCR7) and mutational analysis of the DHCR7 gene in SLOS patients have been recently reported. [6][7][8][9] Nineteen different mutations of DHCR7, mostly missense mutations, have been described in 19 SLOS patients to date. Although a clear-cut phenotype/ genotype correlation cannot be established, homozygosity for mutations resulting in a severe disruption of DHCR7, eg those affecting the highly conserved carboxyl-terminal part of the protein, seems to cause the SLOS type II.…”
Section: Introductionmentioning
confidence: 99%
“…This allows for the biochemical diagnosis of the syndrome. 9 Recently the gene coding for DHCR7 has been cloned 14 and mutations in the gene were identified in all patients with biochemically confirmed SLOS. [15][16][17][18][19][20] The mutational spectrum in the DHCR7 gene from a large group of patients with SLOS has been determined and a genotype-phenotype correlation has been established.…”
Section: Introductionmentioning
confidence: 99%
“…As a cholesterol-synthesising enzyme, interest has grown in DHCR7 since its discovery as the product of the gene mutated in the Smith-LemliOpitz syndrome (SLOS) Wassif et al, 1998;De Brasi et al, 1999), which was first identified in 1964 as a recessive malformation/mental retardation syndrome (Nowaczyk and Waye, 2001;Prasad et al, 2002;Jira et al, 2003;Nowaczyk et al, 2004). Until now, isolation of DHCR7 cDNA has been reported for several species including humans, mice Moebius et al, 1998), rats (Bae et al, 1999), and Arabidopsis (Lecain et al, 1996). Experimental trials have attempted to understand the molecular mechanism of the SLOS mutations, and deficient Hedgehog signaling has been suggested as a possible contributing phenomenon (Cooper et al, 2003;Yu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%